An ambispective observational study on antibiotics in pulmonology department in a tertiary care hospital - Gupta, Nikita; Singarapu, Swetha; Ahmed, M. Ilham; Pasupuleti, Hema; Fatima, Sameera (International Journal Of Community Medicine And Public Health, 2024)
Background: Respiratory tract infections (RTIs) caused by various viruses and bacteria are a major cause of morbidity and mortality worldwide. Although they are usually more severe in children, the elderly and people with weakened immune systems, people of all ages and backgrounds are susceptible to these infections. Antibiotics are commonly prescribed for RTIs in primary care in adults and children. The main purpose of this study is to monitor the use of different antibiotics for respiratory infections. Methods: It is an ambispective observational study, during which data are collected on specially designed data collection forms. The study lasted 6 months (from December 2022 to May 2023). Results: The source of data is a total of 100 patients who were prescribed at least one dose of antibiotics. Out of 100 people, 53% were men and 47% were women. LRTI and URTI are the most common conditions for which antibiotics are prescribed, and we found that the most commonly prescribed antibiotics are a higher percentage of patients using cephalosporins. Of the various cephalosporins, the most commonly prescribed is ceftriaxone, a third-generation cephalosporin. Conclusions: From this particular observational study, we concluded that the most frequently prescribed antibiotics for respiratory infections were cephalosporins, ceftriaxone, third-generation cephalosporins were most frequently prescribed, followed by macrolides, penicillin, tetracyclines, lincomycin, fluoroquinolones, oxazolidinones. The use of antibiotics helps to improve patient care by reducing side effects such as antibiotic resistance, hypersensitivity reactions, respiratory difficulties and risks associated with respiratory infections.